2021
DOI: 10.31234/osf.io/7s962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

”My Soul Got a Little Bit Cleaner”: Art Experience in Videogames

Abstract: Videogames receive increasing acclaim as a medium capable of artistic expression, emotional resonance, and even transformative potential. Yet while discussions concerning the status of games as art have a long history in games research, little is known about the player experience (PX) of games as art, their emotional characteristics, and what impact they may have on players. Drawing from Empirical Aesthetics, we surveyed 174 people about whether they had an art experience with videogames and what emotions they… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…Table 2: An example of eliciting fictional experience recalls using GPT-3. The last researcher question is from Bopp et al [2,3]. For comparison, we also include an example answer from their real human data.…”
Section: What Kinds Of Errors Does Gpt-3 Make?mentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2: An example of eliciting fictional experience recalls using GPT-3. The last researcher question is from Bopp et al [2,3]. For comparison, we also include an example answer from their real human data.…”
Section: What Kinds Of Errors Does Gpt-3 Make?mentioning
confidence: 99%
“…Example human response to the same question [2,3]: It was absolutely beautiful. The game I'm thinking of is Journey.…”
Section: An Interview About Experiencing Video Games As Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the variety of games that were studied in the reviewed records, there are some less studied types of games, including sports or race games, platform games, and indie games. Especially the latter game type is surprising, given that prior research showed the importance of eudaimonia-related emotional experiences to indie game developers (Denisova et al, 2021) and indie games are often related to more artistic, avant-garde narratives, mechanics, and audiovisual elements that can be linked to eudaimonia (Bopp et al, 2021). For example, the indie game Fragile Equilibrium portrays depression and anxiety through abstract, experiential game design in order to provoke emotional resonance which, in turn, builds appreciation and can lead to self-reflection as well as meaning and eudaimonic gratification (Phelps et al, 2020).…”
Section: Variety Of Game Types Eliciting Eudaimoniamentioning
confidence: 99%
“…Finally, we can see scholarship into the aesthetics of gameplay as relevant to the elicitation of eudaimonic experiences. For example, Bopp et al (2021) discussed how players can have artistic experiences from playing games using insights from empirical aesthetics (see Tinio and Smith, 2014), which led to several emotional and eudaimonic reactions, including feelings of beauty, awe, feeling moved, and nostalgia. Possler and Klimmt (2023) also theorized how the aesthetics of games lead to eudaimonic experiences.…”
Section: Aestheticsmentioning
confidence: 99%